2008
DOI: 10.1111/j.1444-2906.2008.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of dietary fish oil with olive oil in young yellowtailSeriola quinqueradiata: effects on growth, muscular fatty acid composition and prevention of dark muscle discoloration during refrigerated storage

Abstract: Dietary fish oil (FO) was replaced by olive oil (OO) in young yellowtail Seriola quinqueradiata to investigate its effects on growth, muscular fatty acid composition and prevention of color deterioration of dark muscle during storage. Yellowtail were fed one of four diets, where FO (80 g/kg diet) was replaced by OO (0, 25, 50 and 100%) for 40 days. No significant difference in growth was seen among the diet groups. In addition, these experimental diets did not affect the proximate compositions of the dorsal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
(56 reference statements)
7
21
2
Order By: Relevance
“…All measurement values were similar to previous experiments (Seno-o et al, 2008;Fukada et al, 2010). Yuzu paste supplementation did not affect the levels of serum components, which suggests no negative effects on fish health.…”
Section: Hemochemical Analysessupporting
confidence: 67%
“…All measurement values were similar to previous experiments (Seno-o et al, 2008;Fukada et al, 2010). Yuzu paste supplementation did not affect the levels of serum components, which suggests no negative effects on fish health.…”
Section: Hemochemical Analysessupporting
confidence: 67%
“…In young yellowtail, the replacement of dietary fish oil with olive oil was found to prevent the red muscle from discoloring because the muscular n-3 highly unsaturated fatty acid level decreased [31]. However, in our study, the color change of the red muscle of the experimental group fed on red pepper was slow even though the fatty acid composition of muscle was almost the same between the control group and the experimental group.…”
Section: Discussioncontrasting
confidence: 69%
“…Increasing evidences have shown that OA has less lipid‐lowering effect and possibly contributes to high levels of TG (Seno‐O et al, ; Steffen, Duprez, Szklo, Guan, & Tsai, ; Truswell & Choudhury, ). In our study, compared with the SO and FO groups, LPL (an exogenous fatty acid transport gene) was highly expressed in liver of the OO group, indicating that more OA uptake was efficiently mediated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EPA and DHA did not promote growth, and high levels of VLCUFAs were found to inhibit growth (Huang et al, ; Olsen & Henderson, ; Stéphan et al, ). The tilapia fed OA had high lipogenesis capacity, which might be beneficial for improved growth, but high levels of OA potentially led to lipid deposition and further cause liver damage (Seno‐O et al, ; Steffen et al, ). Our findings indicated that LA has the moderate capacity of lipogenesis and the lower capacity of lipid catabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation